The effect of exercise on plasma concentrations of inflammatory markers in normal and previously laminitic ponies. (11th September 2013) - Menzies‐Gow, N. J.; Wray, H.; Bailey, S. R.; Harris, P. A.; Elliott, J.
Summary Reasons for performing study The mechanisms underlying predisposition to pasture‐associated laminitis remain unclear; chronic inflammation is implicated, and this may be exacerbated by physical inactivity. Objectives To determine whether exercise affects the inflammatory profile of normal and previously laminitic ponies. Study design Prospective case–control study. Methods The short (1 day) and longer term (14 days) effects of low intensity (10 min walking and 5 min trotting) exercise on plasma inflammatory marker concentrations in normal (NL) and previously laminitic (PL) nonobese ponies (n = 6/group) was determined. Plasma concentrations of TNF‐α, serum amyloid A (SAA), haptoglobin, insulin, adiponectin and fibrinogen were assayed by validated/standard methods. Data were analysed using a linear mixed effects model. Results Before exercise, plasma [adiponectin] was significantly (P = 0.0001) lower in PL (mean ± s.d. 2.4 ± 0.1 ng/l) than in NL (4.03 ± 0.2 ng/l), but exercise had no effect. Previous laminitis and exercise had no effect on plasma [TNF‐α] or [fibrinogen]. Serum amyloid A concentrations in all ponies were significantly (P = 0.00001) reduced after longer term exercise compared to Day 1 values. Plasma [haptoglobin] was significantly (P = 0.00001) higher in PL compared to NL on Day 1. This difference was no longer apparent after longer term exercise, such that [haptoglobin] in PL had decreased to concentrations similar to NL. Following short‐term exercise, all ponies had an initial decrease in serum [insulin] immediately after exercise, followed by an increase peaking 10 min after exercise cessation, before returning to pre‐exercise values. On Day 14 these fluctuations were significantly (P = 0.001) reduced in all ponies. Conclusions Fourteen days of low intensity exercise significantly decreased [SAA] in all ponies and plasma [haptoglobin] in PL such that it was no longer increased compared to NL. Regular low intensity exercise appears to have an anti‐inflammatory effect, which is possibly greater in PL and so may be beneficial in reducing this putative risk factor in pasture‐associated laminitis.